Intrauterine device management by nurses in Primary Health Care - Eliane Kelly Ribeiro da Silva; Helisamara Mota Guedes; Débora Dupas Gonçalves do Nascimento; Albert Schiaveto de Souza; Sebastião Junior Henrique Duarte (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to assess intrauterine device (IUD) management by nurses in Primary Health Care. Method: a descriptive and cross-sectional study. Thirty-one nurses qualified to insert IUDs in Mato Grosso do Sul participated. Data were collected online. Frequency analyses and the binomial test were performed using SPSS 24.0, with a 5% significance level. Results: the majority (83.9%) were female, with a mean age of 37.3 years (±1.35). Of the total, 87.1% had an equipped nursing office and 93.5% used care protocols in their procedures. There was significance in the variables “requests imaging tests”, “prescribes medications” and “performs educational activities” (p<0.001). The monthly mean of insertions was 20.68 (±4.82). Conclusion: IUD management can be improved with investments in physical and material structures. Nurses are also human resources capable of contributing to the reduction of unplanned pregnancies and their consequences.